Syntactic Aspects in Text Messaging - Ong’onda, Nancy Anashia; Matu, Peter Maina; Oloo, Pamela Anyango (Sciedu Press, 2011)
Online interactive media such as text messaging has influenced syntactic aspects of language. In order to determine how text messaging has resulted in paradigm shift in the traditional uses of language, this paper explores the syntactic characteristics of Kenyan text messages. The discussion in this paper is structured around Coupland’s Sociolinguistic theory because syntactic aspects of text messages are influenced by social factors. This theory not only aroused intense discussion within the paradigm on the nature of the discourse of Short Message Service but also steered the subsequent research theoretically and methodologically. The findings reveal that new syntactic structures have permeated into the linguistic continuum of Kenyan texters. Thus, variation analysis shows that there are instances of language (syntactic) variation at every level of English grammar. However, it is apparent that Kenyan text messages are shaped by social variables.
Keywords: Short Message Service; Kenyan; Syntactic; Variation; Use